1985
DOI: 10.1104/pp.78.3.630
|View full text |Cite
|
Sign up to set email alerts
|

Role of ABA in Maturation of Rapeseed Embryos

Abstract: Development of Brassica napus L. cv Tower embryos of different ages cultured in vitro with and without abscisic acid (ABA) was compared with normal development in situ to investipte the role of ABA in embryo maturation. Endogenous ABA levels were measured by radioimmunoassay, and sensitivity to ABA was assayed in terms of its ability to suppress precocious germination and stimulate accumulation of storage protein and storage protein mRNA. During development in situ, the levels of endogenous ABA and 12S storage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
171
1

Year Published

1986
1986
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 279 publications
(180 citation statements)
references
References 18 publications
8
171
1
Order By: Relevance
“…We have confirmed the recent observation [7] that napin mRNA appears a few days before cruciferin mRNA. But, in addition, the possibility of distinguishing between two subfamilies of differently sized napin precursors allowed us to demonstrate that their respective genes are not expressed simultaneously at their maximum level.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We have confirmed the recent observation [7] that napin mRNA appears a few days before cruciferin mRNA. But, in addition, the possibility of distinguishing between two subfamilies of differently sized napin precursors allowed us to demonstrate that their respective genes are not expressed simultaneously at their maximum level.…”
Section: Discussionsupporting
confidence: 91%
“…Our results with radish storage protein mRNA confirm and extent the data recently obtained by studying rapeseed cruciferin and napin mRNA [6,7,191. Rapeseed cruciferin is made from a series of precursors ranging from 43 kDa to 51 kDa as shown by immunoprecipitation of translation products, The rapeseed pattern is more complex than the radish one, as expected from an allotetraploid compared to a diploid.…”
Section: Discussionsupporting
confidence: 89%
“…ABA is required for the accumulation of the 12s seed protein cruciferin in Brassica embryos (Finkelstein et al, 1985), for the continued synthesis of the p subunit of 8-conglycinin in soybean cotyledons (Bray and Beachy, 1985), and the modulation of sunflower helianthinin gene expression (Thomas et al, 1991; A. Nunberg, Z. Li, M. Bogue, J. Vivekananda, A. Reddy, and T.L. Thomas, unpublished results).…”
Section: Dista1 Regulatory Elementsmentioning
confidence: 99%
“…The increase in ABA was greater in seed containing 55% moisture relative to that in the 70% moisture range. (8,(11)(12)(13), with the change in direction occurring at approximately 55% seed moisture (13). Both ABA levels and gene transcripts have been shown to be good markers of seed developmental stage.…”
Section: Germination Potentialmentioning
confidence: 99%
“…Both ABA levels and gene transcripts have been shown to be good markers of seed developmental stage. For example, Crouch and co-workers (8,(11)(12)(13) demonstrated that the levels of ABA and cruciferin mRNA peaked just before the onset of desiccation. Harada and coworkers similarly demonstrated increases in LEA.76 transcripts throughout the desiccation phase (16), and increases in ICL mRNA during the latter stages of desiccation (15).…”
Section: Germination Potentialmentioning
confidence: 99%